2018
DOI: 10.1007/s00109-018-1631-z
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine attenuates sepsis-induced cognitive dysfunction possibly not through inhibiting toll-like receptor 2

Abstract: Sepsis induces neuroinflammation and cognitive impairment, which were attenuated by amantadine. Toll-like receptors 2 mediates these sepsis effects but may not be the major target for amantadine to reduce these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Neuroinflammation is considered as an underlying pathological process for POCD (Cao et al, 2012;Zhang et al, 2014;Zheng et al, 2017). Our study has shown that amantadine attenuates POCD in young adult rats possibly via maintaining GDNF levels (Rocha et al, 2012;Zhang et al, 2014) and sepsis-induced cognitive dysfunction via inhibiting neuroinflammation in young mice (Xing et al, 2018). However, the effects of amantadine on old animals after surgery have not been reported.…”
Section: Introductionmentioning
confidence: 68%
“…Neuroinflammation is considered as an underlying pathological process for POCD (Cao et al, 2012;Zhang et al, 2014;Zheng et al, 2017). Our study has shown that amantadine attenuates POCD in young adult rats possibly via maintaining GDNF levels (Rocha et al, 2012;Zhang et al, 2014) and sepsis-induced cognitive dysfunction via inhibiting neuroinflammation in young mice (Xing et al, 2018). However, the effects of amantadine on old animals after surgery have not been reported.…”
Section: Introductionmentioning
confidence: 68%
“…In addition, it is difficult to select a primary outcome for sample size estimate in a complex basic science study. Thus, we aimed to have a sample size at least 5 for biochemical analysis and 8 for behavior study based on our experience and sample size for these types of studies in the literature [63,64]. Generation of the heterozygous UQCRC1 +/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…One day after the completion of Barnes maze test, mice were subjected to fear conditioning test as we previously described [ 11 , 12 ]. Each mouse was placed into a test chamber wiped with 70% alcohol and exposed to 3 tone-foot shock pairings (tone: 2000 Hz, 85 dB, 30 s; foot shock: 1 mA, 2 s) with an intertrial interval of 1 min in a relatively dark room.…”
Section: Methodsmentioning
confidence: 99%
“…Seven days after surgery, the animals were subjected to Barnes maze in a way we previously described [11,12] to test their spatial learning and memory. Animals were first placed in the middle of a circular platform with 20 equally spaced holes (SD Instruments, San Diego, CA).…”
Section: Barnes Mazementioning
confidence: 99%